Responses of the growth, photosynthetic characteristics, endogenous hormones and antioxidant activity of Carpinus betulus L. seedlings to different light intensities - Zhou, Qi; Zhao, Feng; Zhang, Huihui; Zhu, Zunling (Frontiers in Plant Science, 2022)
Light is an important ecological factor that affects plant growth, survival and distribution. Carpinus betulus L. is native to central Europe and is used as an ornamental plant with strong adaptability. It is an important tree species for landscaping and timber use. What’s more, the antioxidant- and anticancer-related properties of C. betulus leaf extracts are remarkable, that make it a possible raw material for medicine. Light intensity is an important environmental factor affecting the growth and physicochemical changes of C. betulus, but the mechanism of its effect on this species still remains unknown. In this study, the growth, photosynthetic characteristics, endogenous hormones and antioxidant activity responses of C. betulus seedlings to four light intensity gradients (T0: normal light; T1: 75%; T2: 50%; T3: 25% of normal light) were studied after 60 days of shading treatments. The results showed a significant effect of low light intensity on the values of the growth and physiological parameters of C. betulus. The low light intensity caused the inhibition of plant biomass accumulation and the degradation of photosynthetic capacity and stomatal behavior and aggravated the cell membrane lipid peroxidation. However, the plant height growth, leaf area, specific leaf area, photosynthetic pigment content, and contents of GA3 and ABA of C. betulus increased with decreasing light intensity. We found that C. betulus can tolerate mild (T1) and moderate (T2) shading stress by developing photoprotective mechanisms and maintaining relatively high concentrations of organic osmolytes and high antioxidant enzyme activities, but the ability of C. betulus to synthesize osmotic substances and enzymatic antioxidants was impaired under severe shading conditions (T3). Our results suggest that C. betulus can make effective use of low light resources by adjusting its morphology, material distribution, photosynthetic rate and antioxidant enzyme system in suitable low-light environments (50%~75% of normal light); however, light intensity levels that are too low (25% of normal light) will have adverse effects on plant growth. The results of this study provide not only new insights into the response mechanisms of C. betulus to light intensity but also a scientific basis for the cultivation and application of C. betulus in China.